2017
DOI: 10.1136/tobaccocontrol-2017-053912
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco product developments in the Australian market in the 4 years following plain packaging

Abstract: This paper aimed to identify continued and emerging trends in the Australian tobacco market following plain packaging implementation, over a period of substantial increases in tobacco taxes. Since 2012, our surveillance activities (including review of trade product and price lists, ingredient reports submitted by tobacco companies to government and monitoring of the retail environment) found several trends in the factory-made cigarette market. These include the continued release of extra-long and slim cigarett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 10 publications
1
62
0
Order By: Relevance
“…Other trends observed in Australia include marketing of ‘slim’ filters, and ‘natural’-sounding rolling papers and filters33 likely to appeal to young people and women in a similar manner to ‘slim’ cigarettes, small packs and ‘naturally’ branded FM cigarette products 47 48. Other research suggests RYO smokers hold substantial misconceptions about the health effects of RYO cigarettes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other trends observed in Australia include marketing of ‘slim’ filters, and ‘natural’-sounding rolling papers and filters33 likely to appeal to young people and women in a similar manner to ‘slim’ cigarettes, small packs and ‘naturally’ branded FM cigarette products 47 48. Other research suggests RYO smokers hold substantial misconceptions about the health effects of RYO cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…However, as trade journalist White described in a special report for World Tobacco in March 2006,31 a resurgence in marketing of RYO tobacco products has included websites promoting the enjoyment of experimenting with blending various sorts of tobacco,32 the differentiation of new types of tobacco papers of different sizes, colours and flavours, and the packaging of papers featuring designs associated with popular rock bands and best-selling console games 31. A recent examination of the Australian tobacco market following plain packaging implementation in 2012 also found an increase in products using FM cigarette brand names entering the RYO market, and noted the introduction of progressively smaller RYO pouch sizes 33. Innovations that make RYO products more palatable, less unfamiliar, smaller and more affordable are likely to make RYO cigarettes attractive to younger people, including young females who tend to be less experienced smokers and more price sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…However, tobacco industry journals suggest that while larger health warnings and plain packaging reduce the opportunity for brand promotion and make brand-building more difficult, filter characteristics still allow for brand differentiation and marketing. 9,14,15 In Australia and the UK, tobacco companies introduced several new capsule variants after plain packaging was fully implemented 16 -at least five new capsule variants were brought to market in the UK in 2018 alone.…”
Section: Flavour Capsule Cigarettes Continue To Experience Strong Glomentioning
confidence: 99%
“…Whether this is a direct consequence of the legislation is not clear, as research in Australia has also found that tobacco companies revised their brand strategies in anticipation of greater price sensitivity among consumers, including offsetting price rises (i.e. absorbing price increases generated by taxation), offering larger pack sizes with a more affordable price‐per‐cigarette, and more value and super‐value brand variants . Similar trends have been observed in the United Kingdom, and tobacco companies have emphasized the importance of recommended retail price (RRP) to retailers .…”
Section: Introductionmentioning
confidence: 99%